Max Finder mystery : collected casebook - O'Donnell, Liam, 1970-; Cho, Michael (Illustrator) (Toronto, Ont. : Owlkids, 2006)
A collection of mysteries and puzzles involving detectives Max Finder and Alison Santos.
Keywords: Mystery games -- Comic books, strips, etc; Comics (Graphic works).; Detective and mystery comics; Graphic novels